Zasada współdziałania państwa i związków wyznaniowych w prawie polskim - Borecki, Paweł (Studia Prawa Publicznego, 2022)
The principle of cooperation between the state and religious associations gives a positive meaning to the relations of these entities. However, if it is improperly implemented, it risks giving the state a religious character, or the political instrumentalization of religious communities. The principle of cooperation “blurs” the separation of church and state. The cooperation between these entities should be optional, and its goals should be as precise as possible. The principle of cooperation, therefore, deserves relative, not indisputable acceptance. In Polish law, the principle of cooperation between the state and religious associations has both Catholic and secular roots. It became a constitutional and concordat requirement in the sphere of religious relations. At the same time, the Constitution of 1997 and the Concordat of 1993/1998 set out in very general terms the goals of obligatory cooperation between the state and religious associations (the Church). In ordinary legislation, the principle of cooperation between the state and religious associations is articulated primarily in the Act of May 17, 1989 on Guarantees of Freedom of Conscience and Religion, in Individual Religious Acts of 1989–1997, and in the legislation on social welfare and combating social pathologies (alcoholism). The statutory wording is often general and declarative. Detailed legal guarantees for the implementation of the title rule in the aforementioned acts are infrequent. Since 1990, the Church Fund has been such a ﬁnancial and legal guarantee. All in all, its implementation depends to a large extent on the possibilities and will of the partners of the potential cooperation. The correct implementation of the principle of cooperation between the state and religious associations (the Church) is still a challenge in the sphere of religious relations in contemporary Poland.